Konsep Karamah dalam Masyarakat Islam (Konstruksi dan Implikasi Sosial Keagamaan Kewalian Abu Ibrahim Woyla di Aceh) - Putri Nailul Muradi (Jurnal Sosiologi Agama Indonesia (JSAI), 2021)
This study aims to describe the construction and socio-religious implications of Abu Ibrahim Woyla in Aceh. The method used is qualitative with data collection through interviews and literature studies relevant to the research objectives. The results showed that the Acehnese acknowledged the existence of waliyullah in Islam, and they believe that Abu Ibrahim Woyla is a scholar close to Allah, so he has reached the "Waliyullah". The community's belief was driven by several extraordinary events in Abu Ibrahim Woyla, so Acehnese believed that these advantages were a spiritual value gift bestowed on him by Allah. People believe that the karamah on Abu Ibrahim Woyla is a sign of his guardianship. Abu Ibrahim Woyla never directly invited others to follow him. However, there are not a few people who want to follow in his footsteps to be able to stay Istiqomah close to Allah and His messenger.